2017
DOI: 10.1038/s41598-017-02562-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative Effects of Nucleotides on Gastric Cancer via a Novel P2Y6/SOCE/Ca2+/β-catenin Pathway

Abstract: Although purinegic signaling is important in regulating gastric physiological functions, it is currently unknown for its role in gastric cancer (GC). We demonstrate for the first time that the expression of P2Y6 receptors was markedly down-regulated in human GC cells and primary GC tissues compared to normal tissues, while the expression of P2Y2 and P2Y4 receptors was up-regulated in GC cells. Moreover, the expression levels of P2Y6 receptors in GC tissues were correlated to tumor size, differentiation, metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Surprisingly and contrary to CRC and PDAC, P2Y 6 activation in gastric cancer triggered an antiproliferative response through the SOCE/Ca 2+ /β-catenin pathway [55]. W h i l e P 2 R Y 2 m R N A a n d P 2 Y 4 p r o t e i n w e r e overexpressed in GC patients and GC cell lines MKN-45 and SGC-7901, both mRNA and P2Y 6 protein levels were down-regulated.…”
Section: P2y 6 Receptor Promotes Pancreatic and Colorectal Cancer Tummentioning
confidence: 86%
“…Surprisingly and contrary to CRC and PDAC, P2Y 6 activation in gastric cancer triggered an antiproliferative response through the SOCE/Ca 2+ /β-catenin pathway [55]. W h i l e P 2 R Y 2 m R N A a n d P 2 Y 4 p r o t e i n w e r e overexpressed in GC patients and GC cell lines MKN-45 and SGC-7901, both mRNA and P2Y 6 protein levels were down-regulated.…”
Section: P2y 6 Receptor Promotes Pancreatic and Colorectal Cancer Tummentioning
confidence: 86%
“…The serosal solution contained the following: 140-mM Na + , 5.4-mM K + , 1.2-mM Ca 2+ , 1. 2.4 | Measurement of [Ca 2+ ] cyt by digital Ca 2+ imaging Ca 2+ imaging experiments were performed as previously described (Wan et al, 2017). Cells grown on coverslips were loaded with 5-μM Fura-2/AM in physiological salt solution, described below, at room temperature (∼22°C) for 50 min and then washed for 30 min.…”
Section: Ussing Chamber Experimentsmentioning
confidence: 99%
“…Furthermore, (S)-methanocarba nucleotides such as 13 are inactive at the P2Y 14 R, and other methanocarba nucleotides have been shown to be inactive at P2Y 12 R and P2Y 13 R (Supporting Information and ref. 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…52 A recent study demonstrated the anti-proliferative effect of P2Y 6 R activation in gastric cancer. 53,29 …”
Section: Discussionmentioning
confidence: 99%